Pharmacotechnological studies of model samples in the development of a composition of solid gastrosoluble capsules - Vyshnevska, Liliia; Bysaga, Elizaveta; Soldatov, Dmytro (ScienceRise: Pharmaceutical Science, 2019)
Aim: the aim of our work was to experimentally substantiate the choice of auxiliary substances in the development of the composition of solid gastro-soluble capsules for the treatment of diseases of the gastrointestinal tract Methods: pharmacotechnological research methods were used Results. Conducted research on the development of the composition and technology of hard gelatin gastro-soluble capsules with a dry extract under the conventional name urocholum. The effect of a number of auxiliary substances and dry extract on the pharmacotechnological properties of the powder mass for filling capsules by the parameters of moisture absorption, fluidity and bulk density is studied. The optimal ratio of fillers and lubricants relative to the active pharmaceutical substance. The optimal composition of capsules that contain 50 mg of dry extract of urocholum and excipients in the amount of 0.210 g (lactose in the amount of 0.2074 g and magnesium stearate - 0.026 g) has been developed. Analysis of the technological parameters of the capsules made on the basis of the developed composition showed that they meet the requirements of the State Pharmacopoeia of Ukraine. Conclusions: it has been experimentally proved that it is expedient to use in the composition of capsules with a dry extract of the urocholum with complex of excipients - lactose in the amount of 0.2048 g and magnesium stearate - 0.026 g (per capsule)